Isolation and characterizationof cellulose from rice straw and sugarcane bagasse - Wan Norhanis, Ahmad Yarani (Universiti Malaysia Sarawak, UNIMAS, 2009)
Cellulose from two types of lignocellulosic materials, rice straw and sugarcane bagasse were isolated by using two different methods, organosolv treatment and direct dissolution method. In organosolv treatment, solvent system consisted of a mixture of formic acid/acetic acid/water were used as these organic acids were proven to be the most effective solvents in delignification and removal of non-cellulose polysaccharides from the straw and bagasse, and do not have any undesirable side effects on cellulose properties. The bleaching step helped to degrade substantial amounts of residual hemicelluloses and lignin, which enabled the isolation of the cellulose samples of relatively high purity. For the direct dissolution method, a mixture of NaOH, thiourea and urea aqueous solution was used and hold at low temperature to enhance the dissolution power of cellulose. Isolated cellulose from both samples was characterized by SEM, FT-IR and CHN Analyzer.